Pusat Kebudayaan Minangkabau Di Kota Padang Dengan Pendekatan Arsitektur Neo Vernacular - Rido Saputra; Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
West Sumatra is one of the Province in Sumatra Island and Padang as capital City.West Sumatra has lots of potencies such as natural resources and human resources that show highest culture value and local wisdom. Nowaday, era globalization gives impact to degradation of social morality. Then it have decreased care and enthusiasm about local art and culture. Therefore, aim of this research to design West Sumatra Culture Center that include laboratory and display of art culture. Padang is the right choice for the site of culture center because good potency and strategic location, historic value, and culture haritage city. Minangkabau Culture Center is designed by emphasis Neo Vernacular architecture that focuses on shape of mass. Design strategy such as site analycis, room programming, zoning, shape of mass, landscape, interior, and facade. The result of this research is to produce a design of Minangkabau Culture Center that represents minangkabau lokal wisdom itself, especially Rumah Gadang in modern movement.Key words; Culture Center, Minangkabau, Neo Vernacular, Padang.